Investigation ofAzospirillum brasilenseInoculation and Silicon Application on Corn Yield Responses - Galindo, Fernando Shintate [UNESP]; Pagliari, Paulo Humberto; Rodrigues, Willian Lima [UNESP]; Azambuja Pereira, Maikon Richer de [UNESP]; Buzetti, Salatier [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP] (Springer, 2020)
New management practices are needed to help improve the inoculation efficiency of plant growth-promoting bacteria (PGPB). The use of silicon (Si) combined with PGPB can be a useful and sustainable strategy to enhance cereal development under tropical conditions. This research was developed to investigate inoculation methods withAzospirillum brasilensecombined with Si application as a soil amendment in corn. The effects of Si application andA. brasilenseinoculation on plant development and yield were tested on corn for two consecutive years. The study was set up in a Rhodic Hapludox under a no-till system in a completely randomized block design with four replicates. Treatments were tested in a full factorial design (triple factorial 4 x 2 x 2) and included (i) 4 inoculation methods (control, seed, in-furrow, and leaf), (ii) two lime sources (calcium and magnesium silicate and dolomitic limestone), and (iii) two study years (2015/2016 and 2016/2017). Our results showed that seed and in-furrow inoculation were more effective in promoting corn development and greater yield, with an increase of 10.6 and 7.3% in corn grain yield, respectively. Silicate application combined with seed inoculation increased shoot N uptake and root biomass. Also, Si application increased leaf chlorophyll index, stem diameter, and had similar effects on soil properties compared with limestone. Our results showed positive effects on corn growth and productivity as a result of inoculation, while the potential benefits of Si use were less evident.
Keywords: Zea maysL; Inoculation methods; Beneficial element; Plant nutrition; Plant growth-promoting bacteria; Calcium and magnesium silicate